Return to work after sepsis—a German population-based health claims study - Fleischmann-Struzek, Carolin; Ditscheid, Bianka; Rose, Norman; Spoden, Melissa; Wedekind, Lisa; Schlattmann, Peter; Günster, Christian; Reinhart, Konrad; Hartog, Christiane S.; Freytag, Antje (Frontiers in Medicine, 2023)
Background: Long-term impairments after sepsis can impede the return to work in survivors. We aimed to describe rates of return to work 6 and 12 months postsepsis. Methods: This retrospective, population-based cohort study was based on health claims data of the German AOK health insurance of 23.0 million beneficiaries. We included 12-months survivors after hospital-treated sepsis in 2013/2014, who were ≤60 years at the time of the admission and were working in the year presepsis. We assessed the prevalence of return to work (RTW), persistent inability to work and early retirement. Results: Among 7,370 working age sepsis survivors, 69.2% returned to work at 6 months postsepsis, while 22.8% were on sick leave and 8.0% retired early. At 12 months postsepsis, the RTW rate increased to 76.9%, whereas 9.8% were still on sick leave and 13.3% retired early. Survivors who returned to work had a mean of 70 (SD 93) sick leave days in the 12 months post sepsis (median 28 days, IQR 108 days). Conclusion: One out of four working age sepsis survivors do not resume work in the year postsepsis. Specific rehabilitation and targeted aftercare may be opportunities to reduce barriers to RTW after sepsis.